Ultrasound‐Guided Ureteral Stent Removal in Women. (1st October 2016) - Gadzhiev, Nariman; Brovkin, Sergei; Grigoryev, Vladislav; Dmitriev, Vladimir; Korol, Valeriy; Shkarupa, Dmitry; Pisarev, Aleksei; Tagirov, Nair; Malkhasyan, Vigen; Semeniakin, Igor; Khromov-Borisov, Nikita; Petrov, Sergei
Abstract : Objectives: The purpose of this study was to develop a fast, comfortable, and safe method of ureteral stent removal in women. Methods: From February 2014 to July 2015, a retrospective multicenter controlled study including 82 female outpatients was conducted. The control group was composed of 46 patients who underwent stent removal using a 22F cystoscope. The experimental group was composed of 36 patients who underwent stent removal under ultrasound guidance with a 15F spiral‐ending device. Exclusion criteria were pelvic organ prolapse quantification stage II or higher and complicated stents (with migration or encrustation). Results: All studied patients had successful ureteral stent removal. No complications were seen in both groups. Differences between mean visual analog pain scale scores and stent removal durations were statistically significant in favor of the experimental group ( P = .0077 and .0075, respectively). Conclusions: The proposed method for ureteral stent removal in women under ultrasound guidance was shown to be faster and to have lower visual analog pain scale scores, in comparison with removal by a cystoscope, which makes it an attractive option for outpatient urologic praxis in uncomplicated cases, and because it is free of the risk of ionizing radiation and more comfortable, it can be used in pregnant patients.